(untitled) (مجلة الفاروق للعلوم, 2026)
This research aims to evaluate the Heating, Ventilation, and Air Conditioning (HVAC) system in the operating theaters of Nalut Central Hospital and analyze its compliance with approved international standards such as ASHRAE Standard 170 and WHO Guidelines for Surgery. The study adopted a comprehensive analytical approach, combining field visits, technical records review, and direct interviews with staff to assess the system’s performance and adherence to modern operating room requirements. The findings revealed that the previously used non-centralized HVAC system had significantly exceeded its recommended operational lifespan. It failed to achieve essential requirements, including positive pressure, standard Air Change Rates (ACH), or precise temperature/humidity control. Currently, the hospital relies on household air conditioners (Split Units) and natural ventilation, which are entirely incompatible with surgical requirements, posing a significant risk of Surgical Site Infections (SSI). The study concluded that the current system is unable to meet standard specifications, necessitating immediate corrective actions, including the installation of a compliant centralized HVAC system.